Intersection between genes controlling vascularization and angiogenesis in renal cell carcinomas - Souchelnytskyi, S. (Experimental Oncology, 2018)
Aim: To show that application of the systemic analysis may significantly improve comparison of different datasets. Different genes and proteins may converge on the same functional outputs. A comparison of 2 datasets by only identification names of affected molecules may miss that, leading to a conclusion that there is nothing in common for these datasets. Systemic analysis may overcome this limitation, by focusing on functions represented by the identification names. Materials and Methods: Datasets were retrieved from open sources. Systemic analysis of vascularization features and angiogenesis signature was performed by using Cytoscape and its plugs-in. Results: In contrary to the initial statement of the lack of overlap between the vascularization features and the angiogenesis genes-signature in renal carcinomas, we observed an intersection on the functional level. Analysis of the networks built with identification names of vascularization and angiogenesis datasets showed an intersection, which included potent regulators of vessel formation and growth. Conclusion: Analysis of networks may expose functional links, which may be missed by a direct identification names comparison. Key Words: cancer, vascularization, angiogenesis, systemic analysis.